PERLINDUNGAN HUKUM DARI ANCAMAN PIDANA TERHADAP TEKNOLOGI INFORMASI - Ryandi Laksono (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
The development of information technology has caused the world to be borderless and has caused significant social change to take place so fast. The role of technology for human survival improves living standards and provides amazing facilities. Cybercrime can be carried out through the computer network system itself which is the target and the computer itself which is the vehicle for committing crimes. The rapid development of information technology must be anticipated by the laws that govern it. These negative impacts must be anticipated and overcome by laws related to the use of information and communication technology. Legal products related to cyber space are needed to provide security and legal certainty in the use of information, media and communication technology in order to develop optimally. advances in information technology require criminal law as part of the applicable criminal law policy in accordance with the values ??of Indonesian society. Handling of information technology crimes needs to be balanced with the improvement and development of the criminal law system as a whole, which includes the development of the culture, structure and substance of criminal law. In this case, criminal law policy occupies a strategic position in the development of modern criminal law.